Prospective Evaluation of Pain Flares and Time Until Pain Relief Following Musculoskeletal Corticosteroid Injections. (March 2023) - Cushman, Daniel M.; Kobayashi, Jacqueline K.; Wheelwright, John C.; English, Joy; Monson, Nicholas; Teramoto, Masaru; Dunn, Ryan; Lash, Madison; Zarate, Marisol
Background: Corticosteroid injections are used ubiquitously within musculoskeletal medicine. One of the most common side effects is a postinjection pain flare, though little is known regarding this phenomenon. Hypothesis: Some risk factors are related to postinjection pain flare following an ultrasound-guided corticosteroid injection. Study Design: Prospective clinical research study. Level of Evidence: Level 2. Methods: Patients undergoing ultrasound-guided corticosteroid injections in an academic orthopaedic and sports medicine clinic were approached to participate. Patients completed a survey immediately following their injection and again 2 weeks later, asking them about their pain and side effects. A postinjection pain flare was defined as an increase in pain, as defined by the patient. Results: A total of 140 patients completed the entirety of the study, with 29 (20.7%) patients reporting a flare of pain. There was a significant effect of younger age on the development of a pain flare after the injection, estimated as 5.5% decreased odds of developing a flare per year of age ( P < 0.01). Gender, injection location, body mass index (BMI), preinjection pain, and corticosteroid type had no contributing effect. When patients obtained relief following the corticosteroid injection, 60.4% had improved pain within 3 days, whereas over 93.7% obtained relief within a week. Conclusion: Pain flares seem to affect approximately 1 in 5 patients. With increasing age, the likelihood of postinjection pain flare becomes less likely. Sex, injection location, BMI, preinjection pain, and corticosteroid type do not seem to significantly relate to an increase in pain following injection. Clinical Relevance: Corticosteroid injections are common procedures in the orthopaedic and sports medicine settings. Younger patients can be counseled on the higher likelihood of a pain flare following a corticosteroid injection.